2009
DOI: 10.1007/s00787-009-0072-1
|View full text |Cite
|
Sign up to set email alerts
|

The severely impaired do profit most: short-term and long-term predictors of therapeutic change for a parent management training under routine care conditions for children with externalizing problem behavior

Abstract: Short-term and long-term predictors of therapeutic change due to parent management training were investigated. Therapeutic change was defined as the change in outcome measures [externalizing problem behavior and parenting self-efficacy (PSE)] from before treatment to afterward. Three different types of predictors were analyzed: child variables (gender, age, and initial externalizing and internalizing behavior), parent variables (age, initial PSE and parental psychopathology) and socioeconomic status and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
19
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 49 publications
7
19
0
3
Order By: Relevance
“…For disruptive behavior, children who were initially more impaired profited most from behavior-based treatment (August et al 2001;Kazdin and Whitley 2006;Lundahl et al 2006;Reid et al 1999;Stoolmiller et al 2000). This was confirmed by our analyses of predictors of therapeutic change in response to our parent management training for children with externalizing problem behavior (Hautmann et al 2010a). Furthermore, the Conduct Problems Prevention Research Group (2007) reported that only children with the highest initial risk for conduct problems showed significant improvements following intervention, which is why the authors recommended screening.…”
Section: Introductionsupporting
confidence: 61%
“…For disruptive behavior, children who were initially more impaired profited most from behavior-based treatment (August et al 2001;Kazdin and Whitley 2006;Lundahl et al 2006;Reid et al 1999;Stoolmiller et al 2000). This was confirmed by our analyses of predictors of therapeutic change in response to our parent management training for children with externalizing problem behavior (Hautmann et al 2010a). Furthermore, the Conduct Problems Prevention Research Group (2007) reported that only children with the highest initial risk for conduct problems showed significant improvements following intervention, which is why the authors recommended screening.…”
Section: Introductionsupporting
confidence: 61%
“…Gerade schwer beeinträch-tigte Patienten profitierten von den kognitiv-verhaltenstherapeutischen Interventionen und fühlten sich am Ende der Behandlung stabiler. Dieses Ergebnis deckt sich mit den Befunden der Prädik-torstudien von Nakao et al [2001], Hautmann et al [2010] und . Zu beachten ist jedoch, dass das Ausmaß der Symptomveränderung von der Schwere der Belastungsstärke zu Beginn der Therapie abhängig ist.…”
Section: Diskussionunclassified
“…Höhere Eingangsbelastungen korrelieren in verschiedenen Therapiestudien mit besserem Therapieoutcome. Eine Erklärung hierfür könnte ein höherer Leidensdruck sein, der ein wichtiger motivationaler Faktor für das Behandlungsergebnis in Psychotherapien ist [Nakao et al, 2001;Kampman et al, 2008;Hautmann et al, 2010;. Ein weiterer Grund für den geringeren Behandlungserfolg bei Angstpatienten kann ebenfalls eine niedrige Häufigkeit an durchgeführten In-vivoExpositionen sein.…”
Section: Diskussionunclassified
See 1 more Smart Citation
“…There is some support in the literature that parents who attend classes and interact with others through socialization can impact parenting in a positive way, especially with at-risk samples (Deutscher, Fewell, & Gross, 2006;Hautmann et al, 2009;Mayer & Blome, 2013). Some of the most important types of interventions are those that target emotional responsivity, especially on the part of the mother.…”
Section: Introductionmentioning
confidence: 97%